Kafaah Dalam Perkawinan - Muhammad Haikal (Institut Agama Islam Al-Aziziyah Samalanga, 2016)
Kafaah is the correspondence between the prospective husband with the prospective wife for the formation of family sakinah mawaddah warahmah. The most important element of kafaah is the religion where religion here is not limited to worship, but has a noble character and noble character, the science of established religion and strong faith. While the other elements are not the main factor, it depends on the ‘uruf of an area. Kafaah is located in women not from the prospective husband.